Implementasi Pendidikan Karakter dalam Pembelajaran Pendidikan Kewarganegaraan di SMP Advent Remboken - Lidya Julita Sipangkar; Theodorus Pangalila; Telly D. Wua (Tumoutou Social Science Journal, 2026)
The Implementation of Character Education in Civic Education Learning at SMP Advent Remboken. This study aims to describe the implementation of character education in Civic Education (PKn) learning at SMP Advent Remboken. The type of research used is descriptive qualitative, with an approach selected to obtain an in-depth understanding of how character values are applied in the teaching and learning process. Data were collected through interviews, observations, and documentation, then analyzed systematically using data reduction, data presentation, and conclusion drawing. The results of the study indicate that PKn teachers have made efforts to instill character values such as discipline, responsibility, honesty, and cooperation in every learning activity. However, the implementation of character education has not been carried out consistently in every meeting and still depends on the teaching methods used. In addition, strategies that encourage students to actively practice character values in real life are still limited. This study emphasizes the importance of strengthening teaching methods and teacher exemplarity to support the more optimal internalization of character in students.